Working memory load and its impact on space-based and motion-based stimulus-response correspondence (SRC) effects. Issue 2 (17th February 2020) - Styrkowiec, Piotr; Babijew, Adrianna; Dunaj, Karolina; Wierzbicki, Michał
ABSTRACT: If spatial stimulus-response correspondence (SRC) effect results from automatic processes, cognitive load should not affect this effect. However, if spatial SRC effect is based on the interference of cognitive codes, cognitive load should influence it. Furthermore, the motion-based SRC effect should be affected by the cognitive load, as this SRC effect is related to the cognitive codes interference. In this study, participants performed combined tasks for space-based and motion-based SRC effects without working memory load (WML), or under spatial and verbal WML to see if cognitive load affects both SRC effects or just one. Results demonstrated that space-based SRC remained intact from WML, while the motion-based SRC was influenced by WML, although only in limited degree. This supports the notion that automatic processes underlie space-based SRC effect, whereas the motion-based SRC effect is related to cognitive codes interference, but the latter requires further investigation.